4 - The Sphere In-between: Najib Mahfuz on Power, Status and Authority in Africa’s Public Sphere: https://doi.org/10.4314/ad.v34i2.57371 - Ayinde, Oladosu Afis (Africa Development, 2009)
This paper is hinged on the following propositions: in no other region in Africa are the arguments about the role of the artist in the ‘public’ sphere more intense as in North Africa. The problematic of what constitutes the ‘public’ sphere in North Africa is circumscribed by the struggle for and the contest over ‘power’, ‘status’ and ‘authority’; the attempt by North African writers, particularly Najib Mahfuz (d. 2006), to mirror the socio-political and cultural fissures and contradictions in the public sphere usually leads to conflict not only over what constitutes the ‘public sphere’ and who governs it, but equally on how the ‘private’ and the sphere ‘in-between’ could be reclaimed for the ‘public good’. In grappling with the foregoing, the paper rereads Najib Mahfuz’s Awld Hratin 1959). In reading for ‘meaning’ and the ‘meaning of meaning’ in Awld Hratin, the paper pays attention to the socio-political and cultural codes provided by Najib Mahfuz, even as it searches for possible theoretical insights that the works of Arab-African and Euro-American writers including Ibn Qayyim, Abdul Qhir al-Jurjn, Edward Said, Michel Foucault and Benhabib could yield in an excursus which probes into how the trialectic of power, status and authority continues to shape the ‘public’, the ‘private’ and the sphere ‘in-between’ of Egyptian society.